Pengaruh Audit Kepatuhan Prosedur Pelayanan terhadap Tingkat Kepuasan Pasien pada Puskesmas Prambon Kab. Nganjuk - Moh. Ilham Cholid; Fauziyah, Fauziyah; Beby Hilda Agustin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of compliance audit on service procedures toward patient satisfaction at Prambon Public Health Center, Nganjuk Regency. The research is driven by concerns over a decline in the average number of patients in 2024 compared to previous years. This decline in patient visits is a key issue that prompted the need to investigate the relationship between compliance audits in service procedures and the resulting impact on patient satisfaction. A descriptive quantitative approach was used in this study, with 100 respondents for each variable. The sample was determined using probability sampling with a simple random sampling technique, involving both employees and patients who visited the health center during the period between 2021 and 2024. Data were collected through questionnaires, observations, and interviews to ensure a comprehensive understanding of the issue. The regression analysis revealed that service compliance audits have a significant impact on patient satisfaction, contributing 56.67% to the overall patient experience. This finding suggests that improving the service procedures through compliance audits can be a key factor in enhancing patient satisfaction at Prambon Public Health Center. The results of this study provide important insights for healthcare administrators, indicating that regular compliance audits should be integrated into healthcare management practices to maintain and improve patient satisfaction.